To find the equation of the line after it has been translated, we can follow these steps:
-
Identify the original line: The original line is given by the equation \( y = -x + 1 \).
-
Translate the line:
-
Translate 1 unit to the right: To translate the line 1 unit to the right, we replace \( x \) with \( x - 1 \). So, we substitute \( x - 1 \) into the original equation: \[ y = - (x - 1) + 1 = -x + 1 + 1 = -x + 2 \]
-
Translate 2 units up: To translate the line 2 units up, we add 2 to the entire equation: \[ y = -x + 2 + 2 = -x + 4 \]
-
-
Final equation: After both translations, the new equation is \( y = -x + 4 \).
Therefore, the equation of the translated line is \(\boxed{A}\) \(y = -x + 4\).